2021
DOI: 10.3390/socsci10100378
|View full text |Cite
|
Sign up to set email alerts
|

Using the National Incident-Based Reporting System (NIBRS) to Study Animal Cruelty: Preliminary Results (2016–2019)

Abstract: On 1 January 2016, the Federal Bureau of Investigation (FBI) began collecting data on crimes involving animal cruelty from law enforcement agencies that participate in the National Incident-Based Reporting System (NIBRS) in the United States (U.S.). Prior to 2016, such crimes either went unreported or were lumped into an “all other offenses” category, making it difficult to understand who was committing these crimes and whether there were any connections between crimes perpetrated against animals and crimes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Here, we need refer only to a recent study by Palais (2021), who had privileged access to NIBRS data files through her work at the AWI. She reported that, in 2018 and 2019, only 8% of animal cruelty incidents in NIBRS had other crimes associated with them.…”
Section: Does Animal Cruelty Covary With Ihv?mentioning
confidence: 99%
“…Here, we need refer only to a recent study by Palais (2021), who had privileged access to NIBRS data files through her work at the AWI. She reported that, in 2018 and 2019, only 8% of animal cruelty incidents in NIBRS had other crimes associated with them.…”
Section: Does Animal Cruelty Covary With Ihv?mentioning
confidence: 99%